THE INFLUENCE OF PARTICIPATORY LEADERSHIP STYLE AND ORGANIZATIONAL CLIMATE ON EMPLOYEE JOB SATISFACTION AT PT. DESANTA MULIAVISITAMA, SERANG - Adissya Maya Andara (Amal Insani Foundation, 2021)
The purpose of this study was to determine the effect of participatory leadership style on employee satisfaction, to determine the effect of organizational climate on employee satisfaction and to determine the effect of participatory leadership style and organizational climate together on employee job satisfaction at PT. Muliavisitama Desanta in Serang City. This research uses a quantitative approach. As for the population in this study are employees of PT. The Desanta of Muliavisitama, totaling 34 people. Saturated sampling technique is a sampling technique when all members of the population are used as samples so that the sample used in this study is 34 people. The results of this study in the first hypothesis obtained that tcount > ttable (2.433 > 2.037) with a significance level of <0.05 so that there is a significant influence between participatory leadership style on job satisfaction at PT. Desanta Muliavisitama Serang City, the second hypothesis obtained the results tcount > ttable (4.572 > 2.037) with a significance level of <0.05 so that there is a significant influence between organizational climate on job satisfaction at PT. Desanta Muliavisitama Serang City, the third hypothesis is obtained by Fcount > Ftable (11,833 > 3,305) with a significance level of < 0.05 so that there is a significant effect of participatory leadership style and organizational climate on job satisfaction. The conclusion of this study on the first hypothesis there is a significant influence between participatory leadership style on job satisfaction at PT. Muliavisitama Village, Serang City. The second hypothesis has a significant influence between organizational climate on job satisfaction at PT. Muliavisitama Village, Serang City. The third hypothesis is that there is an influence between participatory leadership style and organizational climate on job satisfaction at PT. Muliavisitama Village, Serang City